An Outbreak Investigation of Influenza A (H1N1 and H3N2) in an Elementary School, Chachoengsao Province, Thailand, June-July 2024 - Chareonrungrueangchai, Kridsada; Arthuaikaeo, Waraphon (Disease Control Journal, 2026)
On June 20, 2024, the Chachoengsao Provincial Public Health Office (CPPHO) was notified of a cluster of influenza-like illness cases among students at a local elementary school. The CPPHO initiated an investigation to confirm the diagnosis and outbreak, determine the distribution of the disease, identify risk factors and recommend control measures. The study employed a descriptive epidemiological study, including reviewing medical records for the influenza situation in Mueang District and Chachoengsao Province. Further case findings were conducted by interviewing school nurses, teachers and students. Additionally, samples were collected for viral genetic testing. Environmental surveys were also conducted at the school. A case-control study was performed to identify risk factors for the outbreak. The school had 2,373 students and 170 teachers and staff. A total of 131 cases were identified, resulting in an attack rate of 5.15%. A total of 14.50% of patients required inpatient care, and the case fatality rate was zero. The three most common symptoms were fever (100%), cough (92.62%), and rhinorrhea (72.95%). Laboratory tests confirmed one case of Influenza A H1N1 and three cases of Influenza A H3N2 out of four specimens tested. The key risk factors identified were close household contact, participation in the teacher appreciation ceremony, the lack of hand hygiene prior to eating (Adjusted Odds Ratio [AOR] 5.25, p=0.011), sitting near students with influenza-like symptoms (AOR 3.52, p=0.002), and using air-conditioned classrooms (AOR 3.77, p=0.001). The outbreak of Influenza A H1N1 and A H3N2 at the school was confirmed. Key risk factors included close contact with sick family members, the teacher appreciation ceremony, poor hand hygiene, proximity to symptomatic individuals, and the use of air conditioning in classrooms. The CPPHO intervened by performing a disease investigation, educating on sanitary and safe food handling practices, and providing medical supplies for control. Consequently, the outbreak's severity was reduced, and it was ultimately terminated.